5 - Transformations in Beliefs and Practices of Ecological Inviolability: Historical and Contemporary Perspectives on Mamfe- Akuapem Sacred Forest in Ghana - Kwabena Akurang-Parry (Afrika Zamani, 2022)
Sacred forests, also known as ethnoforests or forest groves, in Africa are a part of the construction of the cosmology of Africans and their effort to seek ecological harmony and biodiversity equilibrium. In sum, sacred forests are sites of deities and ancestors; ritual discourse and genealogical affirmations; and superstructures of social formations, ontology and eschatology. Much of what we know about sacred forests in Ghana and their significance comes from botanists, environmentalists, agriculturalists, anthropologists and archeologists. For their part, historians have shied away from studying sacred forests because of the paucity of written sources: colonial reports and Euro-Christian missionary accounts did not have cogent narratives on sacred forests. At best, colonial agents and Christian missionaries marginally framed African sacred forests in pejorative connotations and dismissed them as atavistic monuments of fetishised sites. What is not in doubt, based on oral history and oral tradition, in fact, major historical sources, is that African sacred forests have utilitarian uses as sites of sustained conservation. This article examines the history of transformation in beliefs and practices associated with a 150-year old sacred forest in Mamfe Akuapem, Ghana. The central thesis that informs the study is that African sacred forests, broadly framed as forest conservation, were closely intertwined with deification of land reserved for biodiversity and shaped by ontological beliefs.